2021
DOI: 10.3390/app11167638
|View full text |Cite
|
Sign up to set email alerts
|

Basic Chemical Composition and Concentration of Selected Bioactive Compounds in Leaves of Black, Red and White Currant

Abstract: The aim of this study was to determine the basic chemical composition, the content of bioactive compounds and antioxidant activity in currant leaves. The leaves of black, red and white currant shrubs were collected in May, and in the beginning of June, July and August, for two years between 2018 and 2019. The proximate analysis, including dry matter, protein, fat, ash and total carbohydrates, was determined. In addition, the content of the polyphenols and the total antioxidant activity using ABTS, DPPH and FRA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Regarding the range of antioxidant capacity obtained with the different assays, our values are slightly higher than those of Teleszko and Wojdylo [ 58 ], who reported an antioxidant capacity for blackcurrant leaves of 329.1 and 191.6 µmol TE/g dw by the ABTS and FRAP assays, respectively, and than the DPPH value of 200.3 µmol TE/g dw reported by Katsube et al [ 59 ]. On the other hand, Ziobroń et al [ 60 ] reported significantly higher values obtained with the ABTS, DPPH and FRAP assays than most of the previously reported ones, reaching even 7877.82 µmol TE/g dw for the DPPH radical scavenging capacity of blackcurrant leaves, and attributed them to differences in the extraction process, as the authors carried out a 2 h extraction in a water bath shaker using acidified methanol.…”
Section: Resultsmentioning
confidence: 85%
“…Regarding the range of antioxidant capacity obtained with the different assays, our values are slightly higher than those of Teleszko and Wojdylo [ 58 ], who reported an antioxidant capacity for blackcurrant leaves of 329.1 and 191.6 µmol TE/g dw by the ABTS and FRAP assays, respectively, and than the DPPH value of 200.3 µmol TE/g dw reported by Katsube et al [ 59 ]. On the other hand, Ziobroń et al [ 60 ] reported significantly higher values obtained with the ABTS, DPPH and FRAP assays than most of the previously reported ones, reaching even 7877.82 µmol TE/g dw for the DPPH radical scavenging capacity of blackcurrant leaves, and attributed them to differences in the extraction process, as the authors carried out a 2 h extraction in a water bath shaker using acidified methanol.…”
Section: Resultsmentioning
confidence: 85%
“…Te Ca content in the leaves of fruit crops [50][51][52] is lower than in berry crops [53]. Te leaves of red currants are rich in calcium, potassium, and magnesium, and the content of these elements depends on the date of leaf collection [54][55][56][57][58]. A low seasonal variability of the Ca content in currant leaves is shown in Figure 2.…”
Section: Efect Of Foliar Calcium Treatments On Vegetative Massmentioning
confidence: 98%
“…Ref. [31] reported that the leaves of currant plants exhibit stronger anti-inflammatory activity due to their increased antioxidant capacity compared with fruits. The same authors expressed the antioxidant activity using the ABTS, DPPH, and FRAP methods and found that the strongest properties were related to the DPPH radical.…”
Section: Blackcurrant Extracts (Fruits Pomace and Leaves): Antioxidan...mentioning
confidence: 99%